Biru hijaunya Royal Belum sebuah dokumentasi Eksplorasi Seni Royal Belum = Blue green of The Royal Belum : documentation of The Royal Belum Art Exploration - Zakaria Ali (Yayasan Perak, 2006)
"Blue Green of the Royal Belum" exhibition and art exploration is most meaningful to the members of the Perak Artists Association who put so much time and effort to make it a reality. The participation of artists from many parts of the country posed a challenge to the organizers. Such collaboration succeeds as the results of joined efforts of all concerned.